JACOBI TRANSFORM OF \((ν, γ, p)\)-JACOBI–LIPSCHITZ FUNCTIONS IN THE SPACE \(L^{p}(\mathbb{R}^{+},Δ_{(α,β)}(t) dt)\) - Mohamed El Hamma; Hamad Sidi Lafdal; Nisrine Djellab; Chaimaa Khalil (Ural Mathematical Journal, 2019)
Using a generalized translation operator, we obtain an analog of Younis' theorem [Theorem 5.2, Younis M.S. Fourier transforms of Dini–Lipschitz functions, Int. J. Math. Math. Sci., 1986] for the Jacobi transform for functions from the \((ν, γ, p)\)-Jacobi–Lipschitz class in the space \(L^{p}(\mathbb{R}^{+},Δ_{(α,β)}(t)dt)\).